Analisis Kepuasan Konsumen Terhadap Produk Keripik Salak UMKM Salak Cristal Di Kecamatan Turi Kabupaten Sleman Yogyakarta (Forum Agribisnis, 2020)
UMKM Salak Cristal is an agro-industry that is engaged in processing salak into various processed salak products. UMKM Salak Cristal has offline and online sales, but less consumer noticed and marketing strategies. UMKM Salak Cristal is not the only salak manufacture producer in Sleman. Therefore it makes UMKM Salak Cristal need information on customer satisfaction to develop appropriate marketing strategies to know changes in consumer needs and achieve customer satisfaction. Accordingly, researchers need to analyze customer satisfaction to help UMKM Salak Cristal in developing the right marketing strategy. This study aimed to 1) Analyze the level of satisfaction with salak chips at UMKM Salak Cristal Turi District, Sleman Regency, Yogyakarta; 2) Determine the marketing strategies that can be done in UMKM Salak Cristal Turi District, Sleman Regency, Yogyakarta. The method of this research used survey method and the sampling method used in this study was the Non-probability sampling method with the accidental sampling technique. A total of 100 respondents were calculated using a linear time function formula. The methods of this research are used Important Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that: 1) Customer satisfaction to salak chips product in UMKM Salak Cristal is on the criterion of satisfaction, 2) Product attributes that must be prioritized to be improved are taste variations, sales and online promotions, store locations, employee uniforms, neat-looking employees, payment processing, displays adjust of products, and product price tags.